Comparison of Visual Acuity and Stereoacuity Outcomes with Vision Therapy between within- and Beyond-Critical-Period in Amblyopic Patients: A Pilot Study - Rinkal Suwal; Mahesh Kumar Dev; Ajit Thakur; Hira Nath Dahal; Bijay Khatri; Deepak Khadka; Arjun Shrestha; Samata Sharma; Ang Jangmu Lama; Purushottam Joshi (TNOA Journal of Ophthalmic Science and Research)
Purpose: To compare visual acuity (VA) and near stereoacuity before and after active vision therapy (AVT) in amblyopic patients, specifically those with anisometropic, strabismic or combined mechanism amblyopia, both in within-critical-period and beyond-critical-period. Methods: This study included 18 patients with amblyopia (anisometropic, n = 7; strabismic, n = 4; and combined amblyopia, n = 7). Patients were categorized into two groups: 10 patients within-critical-period (≤8 years, mean age ± SD, 7.1 ± 0.74 years; range, 6 to 8 years) and 8 patients beyond-critical-period (>8 years, 20.5 ± 10.17 years; range, 9 to 38 years). All patients underwent AVT in three phases: monocular phase, biocular phase and binocular. Each phase lasted for approximately 1 month. Each patient underwent AVT for 1 hour per day on alternate days for 3 months, accounting for a total of 36 sessions. Distance VA in each eye and stereoacuity at near were assessed before commencing AVT and on the last day of the therapy session. Results: In amblyopic eye, AVT led to a mean improvement in distance VA of 0.35 ± 0.12 logMAR in within-critical-period (P = 0.001), while 0.34 ± 0.10 logMAR in beyond-critical-period (P = 0.005), with no significant differences between groups (P = 0.83). The mean improvement in stereoacuity was 0.99 ± 0.32 log seconds of arc (P = 0.005) for those within-critical-period and 0.76 ± 0.37 log seconds of arc (P = 0.012) for those beyond-critical-period, also with no significant difference between these two groups (P = 0.21). Conclusions: AVT could enhance VA in patients with anisometropic and strabismic/combined amblyopia, as well as near stereoacuity in patients with anisometropic amblyopia both within-critical-period and beyond-critical-period.